Performance Evaluation of a Department in the Manufacturing Industry Based on Balanced Scorecard - Utomo, Setiyo; Anisa, Nurfa; Sunyoto, Sunyoto (Formosa Journal of Applied Sciences, 2024)
The success of a company, especially in the manufacturing industry, is closely linked to the performance of each department. The final objective of this research is to determine KPIs, measure department performance on each KPI based on the perspective of a Balanced Scorecard-based performance assessment approach, and then determine achievements. The process of generating Key Performance Indicators (KPIs) commences with conducting unstructured interviews to get KPIs for each perspective. Subsequently, a survey was devised to conduct a systematic evaluation of Key Performance Indicators (KPIs) for each perspective, employing the Analytical Hierarchy Process methodology. The computations yielded weights for the four perspectives: financial, customer, learning, and internal business process. Each perspective was assigned a weight value of 0.25, 0.50, 0.125, and 0.125, respectively.